Designing Criteria for the Evaluation Research Findings in the Field of Social Science and Humanity: some Theoretical Issues - Thu Trang, Nguyen; Thi Ngoc Anh, Nguyen; Thi Quynh Anh, Nguyen; Tien Anh, Tran (VNU Journal of Science: Policy and Management Studies, 2023)
As society evolves, so do people's needs for increasing awareness and knowledge. This is the driving force behind scientific advancement, including social sciences and humanities. The findings of humanities and social science research have made significant contributions to the ideological and scientific foundations of policymaking and development programs. Due to the distinctiveness of originality and creativity with varied values from scientific values, social practical values, informational values, etc., scientific and technical activities need to be identified, managed, and evaluated in accordance with the proper concepts, criteria, and standards. In a scientific research institution, evaluating scientific research outcomes is a critical task. One of the most crucial roles of evaluation is to comprehend the true scientific value of research findings. This article's objective is to provide a theoretical foundation for ongoing efforts to develop a comprehensive framework for evaluating research outputs in the humanities and social sciences. Keywords: Evaluation; scientific research findings; evaluation criteria; social science and humanities research; criteria; scientific research outputs.